The gut microbiome and ovarian cysts: a mendelian randomization study - Jiahui Qu; Liying Zhang (Journal of Ovarian Research)
Abstract Recent evidence suggests a potential association between gut microbiome and ovarian diseases; however, the causal relationship with ovarian cysts remains unclear. In this study, we conducted a two-sample Mendelian randomization (MR) analysis to investigate potential causal effects between gut microbial genera and ovarian cysts. We used summary statistics from large-scale genome-wide association studies (GWAS) of the gut microbiome and ovarian cysts. After stringent selection of instrumental variables, MR analyses were performed using Inverse variance weighted (IVW) as the primary method, supplemented by Simple mode, MR-Egger, weighted median, and weighted mode approaches. Sensitivity analyses, including Cochran’s Q test, MR-Egger regression, MR-PRESSO, and "leave-one-out" analysis, were conducted to evaluate the reliability of the results. We identified 17 gut microbial genera with suggestive causal associations with ovarian cysts. Among these, nine genera appeared to be potential risk factors, whereas eight may play a protective role. These findings provide novel insights into microbe-mediated mechanisms and may inform future clinical research on ovarian cysts.